GC-MS analysis, preliminary phytochemical screening, physicochemical analysis and anti-diabetic activity of ethanol extract of Jasminum cuspidatum leaves - Singumsetty Vinay; Shaik Karimulla; Devarajan Saravanan (Bangladesh Pharmacological Society, 2014)
The purpose of the present study was investigating the GC-MS analysis, preliminary phytochemical screening, physicochemical analysis and anti-diabetic activity of ethanol extract of the leaves of Jasminum cuspidatum. The anti-diabetic activity was investigated in streptozotocin-induced diabetes rats with treatment of ethanol extract at the dose level of 200 and 400 mg/kg, which was compared with glibenclamide at a dose level of 4 mg/kg and the parameter measured being the blood glucose, total cholesterol, HDL, LDL, VLDL, triglycerides, and total protein. An oral glucose tolerance test (OGTT) was also investigated in experimental rats. The GC-MS analysis revealed that the ethanol extract contained seven phytoconstituents. Preliminary phytochemical screening showed the presence of triterpenoids, flavonoids, glycosides and steroids. The result of in vivo anti-diabetic activity revealed that the ethanol extract of J. cuspidatum showed significant anti-diabetic activity.